Are Tourists Facilitators of the Movement of Free-Ranging Dogs? - Schüttler, Elke; Jimenez, Jaime E. (My University, 2022)
Simple Summary Free-ranging dogs are of major conservation concern worldwide as they negatively affect wildlife. This is particularly true for the Global South, where dogs even roam free in and around protected areas. Whether tourists who visit those biodiversity-rich areas play a role in facilitating the access of dogs to nature is largely unknown. Using a combined approach of questionnaires with tourists and camera-traps along trekking trails in the Chilean Cape Horn Biosphere Reserve, this study demonstrates that free-ranging dogs indeed followed tourists-even on several day trips-into protected areas. Although scientists and governmental agencies are aware of the problem and responsible pet ownership strategies are beginning to be implemented, the tourism sector must be explicitly integrated into wildlife conservation management strategies. Awareness campaigns promoting the confinement of dogs should be urgently implemented among tourism operators, hostel owners, and the tourists themselves-not only on behalf of wildlife but also to guarantee the attractiveness of green tourism destinations. Dogs are the most abundant carnivores on earth and, as such, negatively impact wildlife. Free-ranging dogs roam in many protected areas, which in turn are often tourist destinations. Whether tourists influence their roaming is largely unexplored but highly relevant to wildlife conservation. To address this question, we obtained (i) 81 completed questionnaires from tourists on their experience with free-ranging dogs in the remote Cape Horn Biosphere Reserve, Chile, and (ii) photographs of three camera-traps placed next to trekking trails (n = 87 trap days). A third of the participants were followed by dogs for up to four days, and 39% saw free-ranging dogs on their hikes, but neither feeding dogs nor fear of them had any influence on whether tourists were followed by dogs. Camera-traps yielded 53 independent dog sequences, recorded 32 individuals plus 14 unidentified dogs, of which only one was leashed, with a frequency of one dog every 28(th) person. In 17% of 53 sequences, dogs were photographed together with hikers carrying large backpacks for several-day trips. We conclude that tourists are facilitators for the movement of dogs and highlight the importance of the engagement of the tourism sector in wildlife conservation in and close to protected areas.
Keywords: camera-trapping; canis lupus familiaris; chile; companion animal; invasive predator; protected area; questionnaire; south america; wildlife management